ANALISIS KEBIASAAN DARI WARGA MENCUCI PIRING DI SALURAN GOT SAWAH DI DESA KORO BHERA KHUSUSNYA DI DUSUN UBA MORO - Khomsaton Dwi Mansoben (Yayasan Literasi Sains Indonesia, 2023)
The purpose of this study was to determine the habits of residents washing dishes in the sewers of the rice fields in Koro Bhera Village and to find out the efforts to overcome the habits of the residents of washing dishes in the sewers of the rice fields, in the village of Koro Bhera. The research method used is descriptive qualitative. The data sources are primary and secondary. Data collection techniques used are observation, interviews, and documentation. The analysis technique is that the data is collected, after that it is grouped, presenting the data, and drawing conclusions. The results of research related to the habits of the Ubamoro community are 1) It has become a habit. 2) the laziness factor, 3) the water supply at home is not enough, 4) it is more convenient to wash dishes in the sewers of the rice fields, and 5) it is more practical. Meanwhile, efforts to overcome the habit of washing dishes in the sewers of the rice fields, in Koro Bhera Village, are hearing how to do socialization related to the importance of healthy living, educating.